2018
DOI: 10.1016/j.bbrc.2017.11.113
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cholesterol level regulates sensitivity of glioblastoma cells against temozolomide-induced cell death by modulation of caspase-8 activation via death receptor 5-accumulation and activation in the plasma membrane lipid raft

Abstract: Development of resistance against temozolomide (TMZ) in glioblastoma (GBM) after continuous treatment with TMZ is one of the critical problems in clinical GBM therapy. Intracellular cholesterol regulates cancer cell biology, but whether intracellular cholesterol is involved in TMZ resistance of GBM cells remains unclear. The involvement of intracellular cholesterol in acquired resistance against TMZ in GBM cells was investigated. Intracellular cholesterol levels were measured in human U251 MG cells with acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Caspase-9 is an important effector of intrinsic or mitochondrial-regulated apoptosis 41 44 . It has been recently reported that TMZ induces caspase-dependent apoptosis in several cancer cells 45 , 46 . Thus, we determined the effects of TMZ-induced MOMP on caspase-9 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-9 is an important effector of intrinsic or mitochondrial-regulated apoptosis 41 44 . It has been recently reported that TMZ induces caspase-dependent apoptosis in several cancer cells 45 , 46 . Thus, we determined the effects of TMZ-induced MOMP on caspase-9 activation.…”
Section: Resultsmentioning
confidence: 99%
“…29 In contrast, Yamamoto et al reported that MCD treatment can inhibit DR5 clustering to lipid rafts and disrupt DR5-caspase-8 complex. 22 The data presented here revealed that the impact of lipids on LMP1/LMP1 interaction was negative. Lipids likely restricted LMP1 in microdomains of internal perinuclear membranes, and inhibited the formation of LMP1/LMP1 complex.…”
Section: Discussionmentioning
confidence: 54%
“…Lambert et al reported that MCD treatment can enhance viability of cells and promote cell growth, such as HaCaT cells and human glioma cells. 22,28,29 In contrast, Onodera et al reported that MCD can cause cytotoxicity in some cells, such as KB cells, Ihara cells, and M213 cells. 30 Anil et al also made an identical result in TNBC cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 48) In addition, our recent report demonstrated statins with clinical concentration rather suppress TMZ-induced GBM cell death. 49) Therefore, it is suggested the antitumor effect of statins against GBM is various and might depend on its concentration of use.…”
Section: Effects Of Simultaneous Treatment With Cholesterol Depletingmentioning
confidence: 99%